Alterations of the bile microbiome in primary sclerosing cholangitis. Issue 4 (26th June 2019) - Liwinski, Timur; Zenouzi, Roman; John, Clara; Ehlken, Hanno; Rühlemann, Malte C; Bang, Corinna; Groth, Stefan; Lieb, Wolfgang; Kantowski, Marcus; Andersen, Nils; Schachschal, Guido; Karlsen, Tom H; et al.
Abstract : Background: Patients with primary sclerosing cholangitis (PSC) display an altered colonic microbiome compared with healthy controls. However, little is known on the bile duct microbiome and its interplay with bile acid metabolism in PSC. Methods: Patients with PSC (n=43) and controls without sclerosing cholangitis (n=22) requiring endoscopic retrograde cholangiography were included prospectively. Leading indications in controls were sporadic choledocholithiasis and papillary adenoma. A total of 260 biospecimens were collected from the oral cavity, duodenal fluid and mucosa and ductal bile. Microbiomes of the upper alimentary tract and ductal bile were profiled by sequencing the 16S-rRNA-encoding gene (V1–V2). Bile fluid bile acid composition was measured by high-performance liquid chromatography mass spectrometry and validated in an external cohort (n=20). Results: The bile fluid harboured a diverse microbiome that was distinct from the oral cavity, the duodenal fluid and duodenal mucosa communities. The upper alimentary tract microbiome differed between PSC patients and controls. However, the strongest differences between PSC patients and controls were observed in the ductal bile fluid, including reduced biodiversity (Shannon entropy, p=0.0127) and increase of pathogen Enterococcus faecalis (FDR=4.18×10 −5 ) in PSC. Enterococcus abundance in ductal bile was strongly correlated with concentration of the noxious secondary bile acid taurolithocholic acid (r=0.60, p=0.0021). Conclusion: PSC is characterised by an altered microbiome of the upper alimentary tract and bile ducts. Biliary dysbiosis is linked with increased concentrations of the proinflammatory and potentially cancerogenic agent taurolithocholic acid.